VD_FINDINFO Jug / 2024 / 472 vom 30. September 2022 - VD Tribunal cantonal (2022)
RÉVISIONDÉCISION, DEMANDE ADRESSÉE À L'AUTORITÉ, NOUVEAU MOYEN DE FAIT, NOUVEAU MOYEN DE PREUVE | 410 al. 1 let. a CPP (CH), 412 al. 1 CPP (CH), 412 al. 2 CPP (CH)